Priority Directions of the Organization and Management of Public Education of Turkestan (Second half of the 19th century - beginning of the 20th century) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article analyzes the priorities of the organization and management of Turkestan people's education. Tsarist Russia, interested in the rapidly developing industry and the use of Turkestan for economic development, planned to conquer the country and expand the foreign market primarily to sell light industrial products and obtain cheap raw materials. The organization and management of public education in the country relied on these goals.